2013
DOI: 10.1080/00222895.2013.818930
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Visual Cues Mediate Aperture Shaping for Grasping and Pantomime-Grasping Tasks

Abstract: The authors examined whether the top-down requirements of dissociating the spatial relations between stimulus and response in a goal-directed grasping task renders the mediation of aperture trajectories via relative visual information. To address that issue, participants grasped differently sized target objects (i.e., grasping condition) and also grasped to a location that was dissociated from the target object (i.e., pantomime-grasping condition). Just noticeable difference (JND) values associated with the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…Reflecting the fact that people typically use both their hands to grasp large objects that are beyond the limit size of their unimanual grasps, the objects used in the current study were considerably larger in size compared to the objects used in previous studies 7, 10–12, 14, 16, 2729 . Therefore, the current findings do not only extend the dissociation between perception and action to a new visuomotor task, but also for a considerably larger range of object sizes, which was previously restricted by the limited finger span inherent to  unimanual grasps 16 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reflecting the fact that people typically use both their hands to grasp large objects that are beyond the limit size of their unimanual grasps, the objects used in the current study were considerably larger in size compared to the objects used in previous studies 7, 10–12, 14, 16, 2729 . Therefore, the current findings do not only extend the dissociation between perception and action to a new visuomotor task, but also for a considerably larger range of object sizes, which was previously restricted by the limited finger span inherent to  unimanual grasps 16 .…”
Section: Discussionmentioning
confidence: 96%
“…Such limitation is likely to affect the results when either very large objects (relative to the aperture span of the task in hand) are presented 17 or when subjects tend to increase their aperture safety margin due to visual uncertainties inherent to the experimental design 15 . Fortunately, most previous studies that looked at the standard deviations during precision grasping were conscious to this issue and used objects of reasonable sizes, within the comfort range of unimanual grasp 7, 10–14, 16, 2729 . Furthermore, two recent studies that directly tackled the issue of biomechanical constrains during pantomimed grasping and during manual estimations by considering individual differences in hand-size showed that when the potential hazard of biomechanical limit is accounted for, standard deviations still provide a sensitive measure of the underlying resolution 16, 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in our original paper, in which we focused our analysis on the effect of Weber's law on MGAs, which are achieved in the second half of the movement trajectory, these studies have measured the effects of Weber's law throughout the entire movement trajectory (Heath, Mulla, Holmes, & Smuskowitz, 2011;Holmes, Lohmus, McKinnon, Mulla, & Heath, 2013;Holmes, Mulla, Binsted, & Heath, 2011). The results have generally replicated our main finding regarding the point in time in which MGA is achieved, but showed that during early stages of the movement (peaking at about 30% of the movement trajectory), and in line with Weber's law, larger SDs were found for bigger compared to smaller objects.…”
Section: Introductionmentioning
confidence: 98%
“…Were pantomime movement self-copying (Goodale et al, 1991;Goodale et al, 1994;Westwood et al, 2000;Milner et al, 2001;Fukui and Inui, 2013;Holmes et al, 2013;Kuntz and Whishaw, 2016), it might be expected that some participants would producing a more realistic movement representation than others. Rather than displaying variability, however, the participants were consistent in reversing the finger sequence and in using a simple up/down movement to represent the string-pulling action.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of hand movements is an area of central interest in the study of motor control, brain organization, robotics and evolution (Debaere et al, 2003;Karl et al, 2012;Karl and Whishaw, 2013;Kilteni and Ehrsson, 2017;Salvietti, 2018;Isa, 2019;Lemon, 2019;Wu et al, 2019). The action/perception theory suggests that there are two neural systems of movement control, an online action-system for real movements and an offline perceptual-system for pantomime movements, mediated by a dorsal stream parietal cortex to motor cortex pathway and by a ventral stream, temporal cortex to motor cortex pathway, respectively (Goodale et al, 1991;Goodale et al, 1994;Westwood et al, 2000;Milner et al, 2001;Fukui and Inui, 2013;Holmes et al, 2013;Kuntz and Whishaw, 2016). One focus of hand studies is on single hand movements, picking up an object, retrieving an item of food for eating, or pointing (Karl et al, 2012;Karl and Whishaw, 2013;Freud et al, 2018;Ingram et al, 2019;Urbán et al, 2019), another is on bilateral hand movements (Kelso et al, 1979;Franz et al, 1991;Donchin et al, 1998;Swinnen, 2002;De Jesus et al, 2018;Osumi et al, 2019;Shih et al, 2019), but real/pantomime differences have not been featured in bilateral hand movement studies.…”
Section: Introductionmentioning
confidence: 99%